صوبہ خیبر پختونخواہ میں غربت کی شرح ، وجوہات اور ان کے خاتمے کا لائحہ عمل، عمر بن عبد العزیز کی انتظامی اصلاحات کے تناظر میں: The Poverty Ratio in KPK Province, Causes, and a Strategy for its Eradication in the Perspective of Umar ibn Abdul Aziz’s Administrative Reforms - Dr. Navid Iqbal, (Al Manhal Research Journal, 2025)
This article addresses the growing issue of poverty in the province of Khyber Pakhtunkhwa, its root causes, and possible solutions considering the exemplary governance of Caliph Umar bin Abdul Aziz (RA). Despite being a province rich in natural resources, agriculture, and educational potential, Khyber Pakhtunkhwa continues to suffer from widespread poverty, economic distress, insecurity, and corruption. The absence of justice leads to the decline of state institutions and public dissatisfaction. In contrast, the era of Umar bin Abdul Aziz (RA) set such unparalleled examples of justice that peace, equality, and prosperity prevailed throughout society. Accountability is also considered a fundamental pillar of a strong and fair system. Umar bin Abdul Aziz (RA) laid the foundation for high-quality governance by first holding himself, his family, and his officials accountable. The misuse of public and state resources has triggered economic instability in the region, directly resulting in poverty and inequality. Umar bin Abdul Aziz (RA) regarded the public treasury (Bayt al-Mal) as a sacred trust and reformed its structure to ensure that national resources were utilized for the welfare of the people. His administration implemented a just system of zakat (almsgiving) to such an extent that it became difficult to find deserving recipients. Insecurity and the closure of educational institutions are also key contributors to poverty. Due to ongoing terrorism and security challenges in Khyber Pakhtunkhwa, many schools—particularly those for girls—have been forced to shut down, severely affecting education. In contrast, the reign of Umar bin Abdul Aziz (RA) established such a level of public safety that people could travel at night without fear, and animals grazed together peacefully. This article will examine four major causes of poverty: (1) lack of justice, (2) absence of accountability, (3) unchecked misuse of public and endowment funds, and (4) insecurity and the closure of educational institutions. It aims to propose solutions to these issues by drawing on the administrative reforms, justice-based governance, and transparent fiscal policies introduced by Umar bin Abdul Aziz (RA)